ANALISIS PERAN SEKTOR INDUSTRI KREATIF TERHADAP PENYERAPAN TENAGA KERJA DI INDONESIA - Hesty Aisyah; Yopi Eka Anroni (Institut Bisnis dan Teknologi Pelita Indonesia, 2018)
This study aims to analyze the role of creative industry sector in the absorption of manpower in the State of Indonesia from 2002 to 2010. Research variables are divided into two, namely the dependent variable (employment absorption) and independent variables (number of firms, total expenditure for labor, and workforce). Then the data used in this research is obtained from secondary data of one of the statistical institutions in Indonesia namely the Central Statistics Agency of West Sumatra Province which has been compiled and summarized in a book